Historical blocking: MM 2021-02-01 (Myanmar) - Voidly (Voidly Global Censorship Index, 2021)
CRITICAL severity censorship detected in Myanmar. Data sourced from ooni-historical-backfill.
Censorship Incident ID: MM-2021-0030. Severity: critical. Confidence: 85%